Photovoltaic activity in a ZnTe/PEO–chitosan blend electrolyte junction for Solar Cells Application - Al-Bat’hi, , Souad A. M.; Arof , A.K. (2012)

(untitled)
Light to electrical Marketability energy conversion is made possible by photovoltaic technology and solar cells. The injection of electrons from a photoexcited state into the conduction band of the semiconductor upon absorption of light forms the basis for electricity generation in the solar cell. solar cells based on liquid electrolytes are widely used, but there are still problems to be solved. Such as electrolyte leakage, solvent evaporation, and high-temperature instability are among the many problems. To solve these problems, solid polymer electrolyte has been used as replacement. A ZnTe/solid polymer junction has been fabricated. The polymer is a blend of 50wt% chitosan and 50wt% polyethylene oxide (PEO). The ionic conductivity of the solid polymer electrolyte is 1.18x10-5 S cm-1 at room temperature. ZnTe was electrodeposited on ITO conducting glass by electrodeposition technique. The polymer film was casted and sandwiched between the ZnTe semiconductor and an ITO glass to form a ZnTe/polymer electrolyte/ITO photovoltaic cell.